The desire of dematerialization of architecture: the plasticity as process - Almeida, Marcela Alves de (Risco - Journal of Architecture and Urbanism, 2011)
This paper selects two papers of the 1990s, ‘End of the century paradigms: the nineties, between fragmentation and compactness’ of Rafael Moneo and ‘Liquid Architecture’ Ignasi de Solà-Morales, to analyze them on the concepts of matter and form worked out by philosopher Vilém Flusser in ‘Form and Material’. Through this analysis seeks to understand the changes brought about by computers on these concepts in order to demystify discourses that indicate to the desire of dematerialization of architecture. It also presents three works that complement the text exemplifying it.